Effect of using external gfrp plates on structurally deficient RC beams - Leung, Hau Y.; Balendran, Ramapillai V. (Journal of Civil Engineering and Management, 2003)
This paper presents some experimental results on the behaviour of flexure- and shear-deficient RC beams strengthened with external glass fibre reinforced polymer (GFRP) plates. Ten number of 2,5 m long over-designed, unplated under-design and plated under-designed beams were examined under four-point bending condition. Experimental results indicated that use of GFRP plates enhanced the strength and deformation capacity of the structurally deficient beams by altering their failure modes. Application of side plates on shear-deficient RC beams appeared to be more effective than using bottom plates on flexure-deficient RC beams. However, without any improvement on concrete compressive capacity, additional shear capacities provided to the beams under the action of side plates increased the likelihood of beam failure by concrete crushing. Simultaneous use of bottom and side plates on flexure- and shear-deficient RC beams could result in reduced deflection. The change in the neutral axis depth and GFRP strain was also addressed.First Published Online: 26 Jul 2012